Evaluation of cytotoxicity of two endodontic cements in a macrophage culture - Queiroz, Celso Emanoel De Souza; Soares, Janir Alves; Leonardo, Renato De Toledo [UNESP]; Carlos, Iracilda Zeponi [UNESP]; Dinelli, Welington [UNESP] (Faculdade De Odontologia De Bauru - USP, 2005)
Compared to gutta-percha, the endodontic cements are used in small quantity to seal root canals, but are indispensable to achieve hermetically sealed margins, where its biocompatibility depends on the sum of responses of each cell present in the periapical region. The object of this study was to evaluate the cytotoxicity of two endodontic cements, one based on epoxy resin (Sealer 26) and the other containing zinc oxide eugenol (Endofill) by using cultured peritoneal macrophages from Swiss mice to measure the induced production of nitric oxide. After solidification and pulverization, aliquots of 100mul of suspension containing 18mg/mL of the respective cements were added to 96-well tissue culture plates containing the tissue culture of macrophages at a concentration of 5.0X10(6) cells/ml. In the positive control group the cell culture was treated with 10mg/mL of lipopolyssaccharide from Escherichia coli 026:B6 and the cell culture alone represented the negative control. After 48 hours of incubation, at 37ºC, in 5% CO2, the cultures were placed in an ELISA automatic reader to evaluate the release of nitric oxide. The production of nitric oxide for cement Sealer 26 was between 36.1 and 313.0 mumols, with a mean of 143.82±111.03mumols, while for the Endofill these values were significantly less (p=0.01), varying from 50.8 to 125.7mumols, with a mean of 80.33±28.42 mumols. In the positive and negative control groups the mean release of nitric oxide was of 162.75mumols and 4.42mumols, respectively. There was no significant difference between the positive control group and cement Sealer 26 (p>0.05). Therefore, the cement Sealer 26 caused significantly greater toxicity to the macrophages, possibly due to the components from the epoxy resin and formaldehyde release during polymerization.

Comparativamente à guta-percha, os cimentos endodônticos são utilizados em pequena quantidade nas obturações dos canais radiculares, mas são imprescindíveis para obtenção do hermético selamento marginal, sendo sua biocompatibilidade dependente do somatório das respostas de cada célula presente na região periapical. Por conseguinte, o objetivo deste estudo foi avaliar em cultura de macrófagos peritoneais de seis camundongos Swiss, a citotoxicidade de dois cimentos endodônticos, um à base de resina epóxica (Sealer 26) e outro contendo óxido de zinco e eugenol (Endofill), quanto a indução da produção de óxido nítrico. Após a presa e pulverização, alíquotas de 100ml da suspensão contendo 18mg/mL dos respectivos cimentos foram adicionados em placa de cultura de tecido de 96 poços, contendo a cultura de macrófagos na concentração de 5,0X10(6) células/ml. Após 48 horas de incubação, a 37ºC, em 5% de CO2, foi feita a leitura em um leitor ELISA automático para se averiguar a liberação de óxido nítrico. Verificou-se, para o cimento Sealer 26, que a produção de óxido nítrico oscilou de 36,1 a 313,0 mimols, com média de 143,82±111,03, enquanto para o Endofill estes valores foram significativamente menores (p=0.01), variando de 50,8 a 125,7, com média de 80.33±28,42 mols. Nos grupos controles positivo e negativo a média de liberação de óxido nítrico foi de 162,75mimols e 4,42mimols, respectivamente. Não houve diferença significativa entre o grupo controle positivo e o cimento Sealer 26 (p>0.05). Portanto, o cimento Sealer 26 causou, significativamente, maior toxicidade aos macrófagos, possivelmente devido aos seus componentes, a exemplo da resina epóxica e ao formaldeído, liberados durante a sua reação de polimerização.
Avaliação da citotoxicidade de dois cimentos endodônticos em cultura de macrófagos
Keywords: Root canal filling materials; Nitric oxide; Macrophages; Materiais obturadores do canal radicular; Óxido nítrico; Macrófagos